2008
DOI: 10.1117/12.815986
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative retrieving of soil organic matter using field spectrometer and hyperspectral remote sensing

Abstract: As the important component of soil, soil organic matter not only provides every nutrient element for crop, but also has determinant effect for forming of soil structure and melioration the soil physical character. Mapping and dating soil organic matter is of great importance in soil use and evaluation. In this study we examine the feasibility of soil organic matter content by using Hyperspectrally reflective remote sensing methodology. This technique was tested in Xiaochang County located in Hubei province. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Optical remote sensing data have been widely used to map the organic matter content in agricultural soils. Numerous studies conducted in various regions and with different types of remote sensing data have demonstrated that SOM content can be detected with different degrees of accuracy [14][15][16][17][18][19][20][21][22][23]. Due to short wavelengths, the optical range only provides information about the very thin soil surface layer [24].…”
Section: Introductionmentioning
confidence: 99%
“…Optical remote sensing data have been widely used to map the organic matter content in agricultural soils. Numerous studies conducted in various regions and with different types of remote sensing data have demonstrated that SOM content can be detected with different degrees of accuracy [14][15][16][17][18][19][20][21][22][23]. Due to short wavelengths, the optical range only provides information about the very thin soil surface layer [24].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperspectral imageries with narrow spectrum within VNIR-SWIR are proved to be an important data source for mapping soil properties [16,17]. Zhuo et al [18] estimated SOM content by using airborne hyperspectral remote sensing, and proved that the result was reliable. However, airborne hyperspectral technology is costly, and it is difficult to achieve continuous images for large areas.…”
Section: Introductionmentioning
confidence: 99%
“…The topographic parameters as plan and profile curvature were used to map the potential areas of denudation, transit, and accumulation of sediments) (10,14), while the hydrologic parameters as the water power index (WPI) were used to measure potential overland flow indicating the possibility of water erosion (10,11,(15)(16)(17)(18)(19). Moreover, various methods for soil degradation characterization were adapted using soil spectral indices derived from remote sensing data (11,(20)(21)(22)(23)(24)(25). Other studies also showed that remote sensing gave very good information about eroded areas, such as soils types, litho-logical units, and vegetation cover (10,(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%